2019
DOI: 10.3389/fgene.2019.01233
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Chemical-Induced Liver Injury In Vivo From In Vitro Gene Expression Data in the Rat: The Case of Thioacetamide Toxicity

Abstract: Consumers are exposed to thousands of chemicals with potentially adverse health effects. However, these chemicals will never be tested for toxicity because of the immense resources needed for animal-based (in vivo) toxicological studies. Today, there are no viable in vitro alternatives to these types of animal studies. To develop an in vitro approach, we investigated whether we could predict in vivo organ injuries in rats with the use of RNA-seq data acquired from tissues early in the development of toxicant-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…In our previous studies [19,25], we found that activation of the fibrogenesis module increased over time in the liver, an effect which we also observed here when comparing fibrogenesis module activation at 9 and 24 h in Table 1. The fibrogenesis module activation score would likely have continued to increase after 24 h, consistent with the observation that this phenotype takes longer than 24 h to become histologically visible.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…In our previous studies [19,25], we found that activation of the fibrogenesis module increased over time in the liver, an effect which we also observed here when comparing fibrogenesis module activation at 9 and 24 h in Table 1. The fibrogenesis module activation score would likely have continued to increase after 24 h, consistent with the observation that this phenotype takes longer than 24 h to become histologically visible.…”
Section: Discussionsupporting
confidence: 85%
“…Extensive efforts have been made to understand the frequently poor correspondence of experimental results between different species or between in vitro and in vivo studies [10,[29][30][31][32]. We have previously used our toxicogenomic approach to predict rat in vivo toxicity endpoints from rat in vitro RNA-seq data with good concordance [25]. A persisting challenge, however, has been to understand the often weak interspecies correlations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations